Theoretical study on epoxide ring‐opening in co2/epoxide copolymerization catalyzed by bifunctional salen‐type cobalt(Iii) complexes: Influence of stereoelectronic factors - Dyduch, Karol; Roznowska, Aleksandra; Srebro‐hooper, Monika; Lee, Bun Yeoul; Michalak, Artur (Catalysts, 2021)
Propylene oxide (PO) binding and ring‐opening reaction with the bifunctional CO2/epox-ide copolymerization catalyst, based on the Co(III)‐salcy complex including two quaternary ammo-nium salts with n‐butyl substituents (N+‐chains) were investigated by Density Functional Theory (DFT) calculations and compared with the model systems without the N+‐chains. The importance of the different possible stereoisomers and the stereoselectivity of these processes for (S)‐ and (R)‐en-antiomers of PO were considered. To explore the conformational space for the real catalyst, a complex approach, developed previously was applied. The calculations for the model systems directly demonstrate that PO‐ring opening proceeds preferentially in trans catalysts’ configuration and no participation of cis‐β isomers is viable; nucleophilic attack at the methylene‐carbon atom is preferred over that at methine‐carbon atom. For the real bifunctional catalyst, with the (S,S)‐configuration of cyclohexane, the results indicate a preference of (R)‐PO ring‐opening over (S)‐PO ring‐opening (ca. 6: 5). Concerning stereoisomers resulting from the orientation of N+‐chains in the real catalyst, different groups of structures participate in the ring‐opening reaction for (R)‐PO, and different for (S)‐ PO. The high population of nonreactive complexes of (R)‐PO may be the key factor responsible for decreasing the activity of the analyzed catalyst in the epoxide ring‐opening reaction.
Keywords: Bifunctional Co(III) catalysts; CO2/epoxide copolymerization; DFT study; Epoxide opening